3D Analytical Tools for Terrain Spatial Objects - Abdul Rahman, Alias; Chen, Tet Khuan (Faculty of Geoinformation Science and Engineering, Universiti Teknologi Malaysia, 2007)
Geographic information system inevitably moves towards handling and manipulating not just two-dimensional data but more than that e.g., three-dimensional (3D) and four-dimensional (4D) spatial objects. At this moment very few GIS systems offer real 3D analytical operations or analyses with the exception of visualization. Buffering is one of the analytical tools that should be available in any 3D GIS system. This paper discusses 3D buffering aspect in details such as the mathematics, the geometry as well as the development of user interface of the 3D buffering. We tested our buffering approach by using photogrammetrically captured datasets. Finally, the paper provides outlook to the proposed work towards the development of advanced 3D analytical solutions in 3D GIS domain.